2022
DOI: 10.48550/arxiv.2203.14464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barrow holographic dark energy with Granda-Oliveros cut-off

A. Oliveros,
M. A. Sabogal,
Mario A. Acero

Abstract: A study on the effects of implementing the Granda-Oliveros infrared cutoff in the recently introduced Barrow Holographic Dark Energy model is presented, and its cosmological evolution is investigated. We find how the deformation parameter, ∆, affects the values of H(z), and find that from this model it is possible to obtain an accelerated expansion regime of the universe at late times. We also obtain that increasing ∆ causes the EoS parameter to transition from quintessence to phantom. In addition, we show tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This entropy model has later been considered as a model for holographic dark energy [387,388] (see also Refs. [389][390][391][392][393][394][395][396][397][398][399][400][401][402][403][404][405][406][407][408]). In the toy model considered, a three-dimensional FIG.…”
Section: T Barrow Entropy Modifications To the Schwarzschild Metricmentioning
confidence: 99%
“…This entropy model has later been considered as a model for holographic dark energy [387,388] (see also Refs. [389][390][391][392][393][394][395][396][397][398][399][400][401][402][403][404][405][406][407][408]). In the toy model considered, a three-dimensional FIG.…”
Section: T Barrow Entropy Modifications To the Schwarzschild Metricmentioning
confidence: 99%
“…The validity and the constraints imposed by the generalized second law of thermodynamics, including the matter-energy content and the horizon entropy, have been investigated in [58]. Additionally, the Barrow holographic DE (BHDE) model was proposed in [59][60][61][62] and has been tested against the latest cosmological data in [63,64]. It was found that BHDE describes very efficiently the late accelerated expansion of the universe, having additionally the correct asymptotic behavior [65].…”
Section: Introductionmentioning
confidence: 99%
“…The validity and the constraints imposed by the generalized second law of thermodynamics, including the matter-energy content and the horizon entropy, were investigated in [58]. Additionally, the Barrow holographic DE (BHDE) model was proposed in [59][60][61][62] and was tested against the latest cosmological data in [63,64]. It was found that BHDE very efficiently describes the late accelerated expansion of the universe, having additionally the correct asymptotic behavior [65].…”
Section: Introductionmentioning
confidence: 99%